In Vitro Protein Digestibility (IVPD) of Three Indonesian Sorghum Varieties Affected by Water Treatment and Incubation Time - Sumiati ,; Leif Hambraeus; Sten- Ake Lieden (Buletin Ilmu Makanan Ternak, 1991)
The objective of this experiment was to study if incubating the water treated grain could improve the in vitro protein digestibility (IVPD) values of three varieties of Indonesian sorghum (UPCA-S1, KD-4, and No. 46 varieties).Each variety of sorghum was divided into four groups of incubation time: 0 day (as a control group), 1, 2, and 3 days. All of the grains were brought into water content of 30% and incubated at 32⁰C.The IVPD values varied with sorghum variety (P<0.05). TheIVPD value of untreated UPCA-S₁ was higher than those of KD-4 and No. 46. The effect of adding water to the grain followed by incubation at 32⁰C for several days signigicantly improved (P<0.05) the IVPD values of all the three varieties.